Efficiency of probiotics in the quality of the effluent of domestic wastewater treated in biodigesters - Mejia Martinez, Elvis Yoel (2021)
The efficiency of the 600 liters standard biodigester was evaluated, as well as the addition of 1 liter, 10 liters and 100 liters of microbial consortiums named probiotics on 13 samples of rural domestic wastewater treated in biodigesters in the Santeño Annex belonging to the El Carmen sector district of Tumán. After the activation of the probiotics, certain concentrations of the microorganisms were added. the microbiological was determined at the beginning of the experiment and after 24, 48 and 96 hours. In the Microbiological quality the concentrations of Thermotolerant Coliforms by the NMP / 100mL technique were determined. It was concluded that 1. The standard biodigester does not perform an efficient treatment in the microbiological quality of rural domestic wastewater, because the MPN value ≥ 2400 / 100mL of the thermotolerant coliforms are above the maximum permissible limits set by DS 004-2017-MINAM. 2. The most notable effect is the addition of 100 liters of microbial consortiums called probiotics, allowed to obtain domestic residual water of better microbiological quality, managed to reduce the thermotolerant coliforms until NMP = 150 / 100mL, value that is below the Maximum Limits permissible according to DS 004-2017-MINAM. 3. The infiltration time for the descent of 1 cm of water sheet is 5 minutes, classified according to theI.S.020 standard (septic tanks) in a middle class terrain.Keywords: Probiotics, residual water, biodigester.